A Quasi-real Virtual Reality Experience: Point Cloud Navigation - Gomes, J.; Eloy, S.; Silva, N.; Resende, R.; Dias, L. (Virtual Aesthetics in Architecture Designing in Mixed Realities, 2021)
This chapter presents a study that aims to explore the possibilities brought about by recent technologies of visualising an existing building survey in a quasi-real way. It therefore discusses two recent technologies that are useful in the ideation stage of architecture design for existing buildings: 3D laser scanning and Immersive Virtual Reality. A 3D scan survey of an existing building undergoing rehabilitation was performed and a technique for visualising the point cloud in an immersive Virtual Reality environment was developed. Point cloud models offer rigorous and consistent information in comparison to traditional surveys. In addition, the use of immersive virtual reality to visualize point clouds provides an experience of the “real” building that would not be possible by any other means except a site visit. We conclude that virtual reality provides designers with an incredible source of authentic building elements that offers them a quasi-real experience. During this experience, designers are transported to a new dimension where not everything from the existing building has a place, but the essence of the building “levitates” in a virtual world.